Estudo da prevalência de transtornos mentais comuns via métodos de classificação - Martinez, Giulia Molina (Universidade Federal de São Carlos, 2024)
The present undergraduate thesis focuses on the study of the association between specific variables and the diagnosis of common mental disorders. To achieve this goal, we examined classification methods, namely decision trees, logistic regression, and random forests. This investigation is preceded by a statistical definition and methodological review of the concepts to be employed, as well as data preprocessing. All computational applications were carried out using the programming language R.
Study of the prevalence of common mental disorders through classification methods
Keywords: Arvores de classificação; Classificação; Florestas aleatórias; Regressão logística; Transtornos mentais comuns; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::ANALISE DE DADOS